The Influence of Learning Model on Chemical Learning Outcomes Viewed from Goal Orientation Participants in Senior High School - Miftah Athor Sanjaya; Asmadi M. Noer; Roza Linda (Journal of Educational Sciences, 2019)
This research was motivated by the difficulty of students in understanding the concepts in chemical material. The goal of this research is to see the differences in learning outcomes between students who are given two different learning models and see it from Goal Oriention (GO) factors owned by students. This research was conducted at SMA Muhammadiyah 01 Pekanbaru City. The variables in this study were the Learning Model and GO characters (independent variables) and chemistry learning outcomes (the dependent variable). The results of data analysis on One Way Anava was a sig. 0.02 for the application of two learning models and the Independent Sample T-Test obtained sig. 0.02 and sig. 0.32. Based on data analysis, it was concluded that student learning outcomes with those taught with the DL model were better than students taught with the PBL model. Learning outcomes MGO students who are taught with the DL model are better than those taught with the PBL model and there is no difference in the learning outcomes of the PGO students who are taught with the PBL learning model with students who are taught using the DL model.